The Analysis of Factors that Influences Purchasing Decisions at Summerz Cafe Surabaya - Fani Rachmawati; Saino (Institute of Computer Science (IOCS), 2021)
This research aims to look into the elements that influence customer buying interest at Summerz Cafe Surabaya. This research method used is quantitative. The populationin this study is consumers of Summerz Cafe Surabaya. Research sampling techniquewith nonprobability sampling strategy with an accidental sampling approach as the research method. The sample in this study was100 consumers of Summerz Cafe Surabaya.Data collection techniques with online questionnaires. Data Analysis assisted by SPSS Software version 16, the analytic approach employed was principal component analysis factor analysis. The findings revealed that: 1) the variables evaluated revealed six aspects that customers in the Summerz Cafe Surabaya examined, namely Product factors (41,53 % ). Factor of Promotion (9,34 % ). Factors affecting services and facilities (6,7 % ). The factor of the Physical Environment (5,7 % ). The factor ofPrice (5,23%). Social factors (5.23%); 2) Social factors become a dominating factor or the most considered by consumers in arousing buying interest in the Summerz Cafe Surabaya (41,53%).